Empowering forest dwellers and managing forests more sustainably in the landscapes of Borneo - Campbell, Bruce M.; Gunarso, Petrus; Kartawinata, K.; Levang, P.; Rhee, S.; Sheil, Douglas; Sist, P.; Wollenberg, Eva Karoline (Food and Agriculture Organization of the United Nations, 2003)
This case study covers work in the Malinau catchment in East Kalimantan, Indonesia, a vast area of primary and secondary forest with scattered villages. The project has evolved to focus on key factors underlying poverty and forest loss. Inappropriate harvesting is reducing biodiversity, limiting regrowth of valuable species, and reducing water quality. The research aims to produce positive local impacts, while at the same time generating international public goods. Integration is achieved through a variety of annual and other meetings where multiple stakeholders, including especially local communities, gather to reflect on progress, and jointly plan for the next year. Conceptual models are used at such meetings to assist in building an integrated understanding of the inter-connected problems and opportunities. Participatory action research (PAR) is a feature of the work, allowing the research partnerships to rapidly adapt to fast-changing circumstances. The results have indicated the cost-effectiveness of reduced impact logging, but the difficulties of establishing and enforcing appropriate policies have proven to be the main factors limiting sustainable forest management. In the current phase of the work further effort will be given to spatial planning, in addition to capacity building of communities and district officials in this area. The research team has already contributed to the official land-use plan for the district, which incorporates some aspects of landscape management derived from the research.